Stop bullying: Evidence from an exploratory factor analysis of dominant bullying behaviors among Malaysian adolescent - Abdul Hamid Busthami Nur; Nurulwahida Azid; Ruzlan Md-Ali; Siti Jaizah Nakman; Tee Tze Kiong; Yee Mei Heong (International Journal of Evaluation and Research in Education (IJERE), 2023)
Bullying, a recurring aggressive and substantial antisocial behavior characterized by a power imbalance can be destructive, and persistent and causes harm. Bullying is a negative behavior on individuals or groups of individuals who are considered weak that occurs more frequently among adolescents between the ages of 13–16. Bullying in schools is a violence that can result in students feeling threatened and powerless. This study was conducted to identify constructs that measure physical, verbal, anti-social, and cyberbullying. A total of 677 samples from a total of 23 secondary schools in the northern peninsula of Malaysia were involved in this cross-sectional survey research design that used a questionnaire to collect the data. Exploratory factor analysis was used to analyze the data. The results showed that four factors namely, physical bully, verbal bullying, antisocial bully, and cyberbullying were prevalent among Malaysian adolescents. The reliability value for each factor was high, which ranged from .73 to .89. Out of four bullying constructs in the study, physical bullying has the highest factor loading. In conclusion, this study has proven that Malaysian adolescents also face bullying where the most dominant bullying behavior for Malaysian adolescents is physical bullying. The data imply that school leaders, the Malaysian Ministry of Education, and the community should view this matter seriously and Malaysian youths should be educated on the dangers of bullying behavior that can have a negative impact on the development of society as a whole.